Evaluación del Sistema de Riego por Aspersión TIPO PIVOTS en Caña de Azúcar (saccharum officinarum) en Irrigación Olmos - León Arteaga, Danae Lizbeth (2017)
The main objective of this work is to evaluate the sprinkler irrigation system type pivots in sugar cane, which has been implemented recently in the Olmos Irrigation project, considering that it presents outstanding advantages in terms of savings in the hand of work, high efficiency, adaptable for cultivation and fertigation etc. Based on the problems observed in the field is decided to analyze the design, operation and performance of the project taking as shown a total of six (06) pivots that are installed in the field and operating. We analyzed agronomical design, hydraulic design in hydrants, pivots, energy costs, implementation costs and automation. As a result, it was also obtained that opting for this method of irrigation solve problems like the amount of water and energy that the project offers, besides that implementing the SCADA system allowed a much easier operation and maintenance, giving the possibility of to irrigate large areas, being feasible the application of fertilizers and chemicals with irrigation water, obtaining a better and profitable production. Finally, the evaluation indicates that to improve it is necessary to place filtering systems in hydrants to avoid the entry of materials that cause damage to the mechanical equipment, as well as the operation and uniformity of sprinklers. By making the corrections detailed by our maintenance team we will be able to optimize the sprinkler irrigation system of the pivots.